2019
DOI: 10.1177/0379572118825163
|View full text |Cite
|
Sign up to set email alerts
|

Maternal and Child Nutrition Status in Rural Communities of Kalalé District, Benin: The Relationship and Risk Factors

Abstract: Background: Double burden of malnutrition (DBM) is an emerging public health concern in urban Benin. However, an understanding of the phenomena in rural areas of the country is lacking. Objectives: To assess the prevalence of DBM and to investigate the sociodemographic and dietary characteristics that differentiate DBM from undernourished children only, overweight/obese mothers only, and normal households in Kalalé district. Methods: A cross-sectional study was conducted on 426 mother-child pairs: nonpregnant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
9
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 47 publications
2
9
0
2
Order By: Relevance
“…The prevalence of stunting is very high at 29.7%, which is close to the national prevalence, and similar to the prevalence of stunting in the West African sub-region (31.4%) (UNICEF and WHO, 2017) and sub-Saharan Africa (Akombi et al, 2017). Our results concur with a recent study in Benin by Alaofè and Asaolu (2019), who reported that 37.6% of children were stunted, 10.1% wasted and 22.8% underweight. According to WHO, the prevalence of 9.8% wasting and 29.7% stunting, in terms of severity, is a medium health concern.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The prevalence of stunting is very high at 29.7%, which is close to the national prevalence, and similar to the prevalence of stunting in the West African sub-region (31.4%) (UNICEF and WHO, 2017) and sub-Saharan Africa (Akombi et al, 2017). Our results concur with a recent study in Benin by Alaofè and Asaolu (2019), who reported that 37.6% of children were stunted, 10.1% wasted and 22.8% underweight. According to WHO, the prevalence of 9.8% wasting and 29.7% stunting, in terms of severity, is a medium health concern.…”
Section: Discussionsupporting
confidence: 93%
“…Approximately 16.9% of mothers in this study were overweight and 7.6% obese, mimicking the national trends from the health survey in 2012. More recently, Alaofè and Asaolu (2019) reported that the rate of overweight/obese mothers was 15.5% in Benin. These figures are similar to others found in the department where Grand-Popo is located (19.9% overweight and 12% obesity) (Enquête Démographique et de Santé, 2012).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,14 Beberapa penelitian terdahulu terkait beban gizi ganda menunjukkan bahwa faktorfaktor yang berhubungan dengan terjadinya beban gizi ganda pada tingkat keluarga secara signifikan merujuk pada faktor langsung dan tak langsung yang berkaitan dengan status gizi, seperti faktor asupan makanan, ketahanan pangan, karakteristik ibu dan anak, tingkat ekonomi keluarga, dan tingkat pendidikan. 5,6,7,15 Selain faktor-faktor tersebut, faktor lingkungan, fasilitas kesehatan, dan wilayah tempat tinggal juga memiliki peran yang penting dalam pengentasan masalah malnutrisi. 16,17,18 Adanya perbedaan demografis, karakteristik dan budaya masyarakat memungkinkan adanya perbedaan faktor-faktor yang berhubungan dengan kejadian beban gizi ganda antar negara.…”
Section: Pendahuluanunclassified
“…rendah juga memiliki peluang lebih besar dan signifikan terhadap masalah beban gizi ganda 7,15,26,44. Hal ini mungkin dapat dikaitkan dengan pentingnya peran pendidikan, pengetahuan, dan praktek terkait pemilihan bahan makanan dengan kandungan gizi yang tepat dan pencegahan timbulnya penyakit yang merupakan kunci utama dalam mencegah terjadinya malnutrisi 41.…”
unclassified